ISSUES OF SOCIAL CONSCIOUSNESS IN THE VIEWS OF CENTRAL ASIAN SCHOLARS - Sobirov Axrorjon Anvar o‘g‘li; Salimov Bakhriddin Lutfullaevich (Ustozlar uchun, 2025)
In the article, the difference of philosophy from other forms of social consciousness is that it examines the world as a whole, studies the general characteristics of nature, shows the ways and methods of knowing the reasons for its development, human thinking and the general laws of society, and its contribution to changing the world. addition is analyzed.